Gamification in Marketing Strategy: A New Way to Build Customer Engagement - Gunawan Gunawan (SEAN Institute, 2023)
This study aims to explore the application of gamification as an innovative marketing strategy to build customer engagement. With increasing market competition and changes in consumer behavior that are more interactive and digitally savvy, companies are required to create engaging marketing experiences that enhance customer loyalty. Gamification, which is the use of game elements in non-game contexts, offers a new and effective approach to increasing customer interaction, motivation, and participation. The research method used is qualitative with a descriptive-analytical approach, examining various case studies and related literature on the implementation of gamification in the marketing world. The results show that gamification is an effective marketing strategy to increase customer engagement and loyalty. By incorporating game elements such as points, challenges, rewards, and leaderboards into apps, websites, or social media platforms, companies can create enjoyable and motivating experiences. This makes customers more interested, more likely to interact frequently with the brand, and more loyal in the long run. Gamification also helps companies voluntarily collect user behavior data to develop more targeted marketing strategies. Amidst intense market competition, this approach becomes a creative solution to build strong consumer relationships and drive sustainable business growth.